The Physiochemical properties, sensory evaluation and shelf life of corn flour supplemented with Acheta gossypii (cricket) flour - Ehoche, Elijah Edache; Oluwafunmi, Akanya; Oluwafunmilola, Adefolalu Folasade (POLTEKKES KEMENKES YOGYAKARTA, 2019)
Most consumed diets are made from corn and are deficient in proteins. Corn flour was made from fermented and dried yellow corn and supplemented with 5 and 10 % proteins of crickets. The diets were analyzed for the following physiochemical properties: swelling index, wettability, bulk density, solubility, and water holding capacity as well as sensory characteristics in a 7 point hedonic scale and the maintaining quality of each diet. Standard methods for physiochemical properties were used, and the microbial assay was also to analyze the diets at refrigerated and non-refrigerated conditions. The swelling index(1.83-2.00 g), gelatinization temperature ( 66.3 -72.3Â°C), wettability (22.0-120 seconds), and bulk density (0.59 - 0.67 mg/mL), significantly increased but solubility (14.1 - 3.00%), and oil-water holding capacity ( 90-65 %) reduced significantly in the cricket supplemented diets over the corn flour ( p< 0.05). The sensory characteristics from both the adult and children scored above average on the 7 points hedonic scale, with a major preference for the 5 % cricket supplemented the diet. It is noteworthy that in the 4 weeks of shelf life experiment, all the diets were found to be devoid of the growth of coliforms, yeast and the only occurrence of the mold is below the harmful threshold except with the 10 % cricket supplemented non-refrigerated diet with the growth of B. subtilis on the 3rd week of the experiment. However, the growth of this bacterium is below a harmful threshold. Proper handling and processing are safest before consumption. Supplementations of corn flour with cricket have been found to improve the nutritional quality of corn and may, therefore, be able to solve the problem of malnutrition.